Factor VIII Procoagulant Antigen in Human Tissues - Kadhom, N; Wolfrom, C; Gautier, M; Allain, J P; Frommel, D (Thrombosis and Haemostasis, 1988)
The localization of factor VIII procoagulant antigen (VIII: Ag) and factor VIII von Willebrand antigen (VWF: Ag) was investigated in human liver, lung, spleen, placenta and umbilical cord, by an immunoperoxidase technique using an avidin biotin complex (ABC). Positive staining for VIII: Ag was observed in the endothelial cells of liver sinusoids, veins and arteries, as well as in the endothelial cells of placenta, lung and spleen. VWF: Ag was detected in the vascular endothelial cells of all the organs explored. The staining intensity of both VIII: Ag and VWF: Ag varied in the different tissues and showed a distinctive pattern of distribution in the liver. VIII: Ag was also observed in the cytoplasm of dysplastic, foetal-like hepatocytes which infiltrated one liver specimen. Our results agree with the view that liver endothelial cells are a major site of Factor VIII (F VIII) storage and secondary release into the circulation. However, the bright staining intensity of VIII: Ag and VWF: Ag in the lung and placenta suggests that these two tissues might also be a substantial source of F VIII.
Keywords: Factor VIII; Tissue localization; Immunoenzymohistology